Beyond borders: The effects of immigrants on value-added trade - Bedassa Tadesse; Roger White (Economies, 2024)
While the effects of immigrants on aggregate trade flows have been extensively examined, the role of immigrants in shaping trade in value added (TiVA) remains underexplored. Employing a panel dataset covering 38 Organization for Economic Co-operation and Development (OECD) member host countries and 64 immigrant home countries spanning 2000-2018 and estimating a random intercept and random slope mixed-effects model, we find that immigrants play a significant role in enhancing the value added from their home countries that is embedded in their host countries' exports to the world. We document these effects at the aggregate level and across sectors (i.e., manufacturing, agriculture, and services). There is, however, considerable variation in the influence of immigrants on TiVA across country pairs. Our findings highlight that immigrants significantly enhance trade sophistication by promoting specialization and upward movement in the value chain, yielding economic benefits for their home and host countries.
Keywords: F22; F14; F23; F10; 330; immigration; productive capacity; trade costs; value-added trade